Performance Analysis of Multiple Pico Hydro Power Generation - Karuppusamy, P. (Journal of Electrical Engineering and Automation, 2020)
Electric energy has become a basic and essential thing in human life. The electricity is not only utilized for entertainment, it also helpful in powering many devices utilized in medicine, emergency and assisting. Generation of electric power is not a simple task in any medium. There are several medium of power generation is possible in the present scenario. At present, renewable source of energy generation has become popular because of its atmosphere friendly nature and reduced cost of installation for generating station. Hydro power generation is one among such method of power generation produces electricity by means of rotating a turbine blades with running water. The traditional hydro power plants were made to produce electric energy from the river water movement and falls water movement. The proposed MPH (Multiple Pico Hydro) power generation scheme is developed to make power generation from the domestic running water flowing in the pipeline of a home or apartment. The produced power is stored to a battery source and inverted in to an alternating current supply for powering the home. To make an efficient model the pico power generators are fixed to multiple pipelines. The performance of the proposed model is analyzed and it can be connected to another renewable energy sources for making a hybrid structure of power generation.